SISTEM INFORMASI UNIT KEGIATAN MAHASISWA PADA STMIK KHARISMA MAKASSAR - Irwan Irwan; Syaiful Rahman; h Anggriani (STMIK KHARISMA Makassar, 2018)
The purpose of this research is to build Student Unit Information System which displays the archives of information that entered from a collection of data that coming from many existing student activity unit as a proof of student activeness in participating campus student activity unit. This research divided into five stages, that is problem identification, data collection, design system, implementation, and testing system. Design system includes system modeling using Data Flow Diagram and data modeling using ERD (Entity Relationship Diagram), then implemented using PHP programming language and MySQL as database then testing on system using black box testing method. From the results of this study produced a web-based applications that can help the students in monitoring the activeness of every existing UKM.